Nexus between Digital Transformation and Cost Management in Nigerian Manufacturing Companies - Abiloro, Rafiyat Bosede; Akinleye, Gideon Tayo; Alabadan, Dinatu Nna; Adesodun, Ruth Bosede; Alabi, Adekunle Adegboyega (Acta Universitatis Danubius. Œconomica, 2024)
This study examined the connection between digital transformation and cost management, focusing on how technology can enhance efficiency and decision-making in Cadbury Nigeria Plc. It specifically assesses the prevailing cost management practices in Cadbury Plc in the context of digital transformation and analyzes the effects of technology-driven cost management strategies on organizational efficiency and decision-making processes within Cadbury Plc.The research method integrated both quantitative and qualitative approaches to investigate the relationships between digital transformation initiatives, technology-enabled cost management strategies, and organizational outcomes. Self-administered questionnaires were distributed to collect primary data from respondents across various departments within Cadbury PLC. The population of the study comprised 250 staff members, with representation from departments such as Production, Sales and Marketing, Finance, Human Resources, Supply Chain Management, Research and Development, Quality Assurance, and Information Technology. The sample size was determined using Yamane's Sample Size statistical techniques. The findings revealed the relationship between digital transformation initiatives, technology-enabled cost management strategies, and organizational outcomes at Cadbury Plc. The regression analysis revealed that the implementation of digital transformation initiatives positively influences the effectiveness of cost management practices, as evidenced by the statistically significant coefficient (β = 0.487, p < 0.001) while the regression result of the technology-enabled cost management strategies has significant relationship (β = 0.296, p = 0.049) on Cadbury efficiency and decision-making. The positive impact observed suggests that Cadbury Plc has successfully leveraged digital initiatives to improve its cost management practices, thereby enhancing operational efficiency and competitiveness. In conclusion, this study provides actionable insights for organizations navigating the complexities of digitalization, emphasizing the importance of strategic technology adoption in enhancing cost management practices and driving organizational success.